Effect of initiation of renal replacement therapy on mortality in acute pancreatitis patients. Issue 47 (20th November 2020) - Zhang, Xing; Cao, Yang; Pan, Chang-Kun; Han, Qiu-Yuan; Guo, Ya-Qi; Song, Ting; Qi, Zhi-Dong; Huang, Rui; Li, Ming; Yang, Zhen-Yu; Zheng, Jun-Bo; Hou, Gui-Ying; et al.
Abstract : Abstract: This study aims to explore effect of initiation of renal replacement therapy (RRT) on mortality in acute pancreatitis (AP) patients. In this study, a total of 92 patients from the surgical intensive care unit (SICU) of the Second Affiliated Hospital of Harbin Medical University who were diagnosed with AP and underwent RRT or not between January 2014 and December 2018 were included in this retrospective study. Demographic and clinical data were obtained on admission to SICU. Patients were divided into early initiation of RRT group ( n  = 44) and delayed initiation of RRT group ( n  = 48). Duration of mechanical ventilation (MV), intra-peritoneal pressure, vasopressors infusion, body temperature, procalcitonin, creatinine, platelet counts, length of hospital stay and prognosis were recorded during hospitalization, and then compared between groups. Patients with delayed initiation of RRT exhibited significantly higher APACHE II score, SOFA score and lower GCS score than those with early initiation of RRT ( P  < 0.001, <0.001,  = 0.04, respectively). No difference in the rest of the baseline data and vasopressors infusion was found. Dose of Norepinephrine, maximum and mean PCT, maximum and mean creatinine, maximum and mean intra-peritoneal pressure, length of hospital stay, prognosis of ICU and hospitalization showed significant difference between groups. Early initiation of RRT may be beneficial for AP patients, which can provide some insight and support for patients' treatment in clinic.